MANAJEMEN BIMBINGAN MANASIK HAJI DALAM MENINGKATKAN KUALITAS JEMAAH HAJI DI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI JAMBI - Fitriani, Eva; Kusnadi, Edy; Hasanah, Neneng (Qaulan Baligha: Jurnal Ilmu Manajemen Dakwah, 2024)
This research is motivated by the management of Hajj ritual guidance to improve the quality of Hajj pilgrims at the Regional Office of the Ministry of Religion, Jambi Province. In terms of improving the quality of Hajj pilgrims, good and appropriate management is needed, especially since every year there is an increase in the number of pilgrims performing the Hajj. Guidance on Hajj rituals will not only have an impact on the congregation but also on social activities in general. The aim of this research is to find out how the Hajj ritual guidance process works to improve the quality of Hajj pilgrims at the Regional Office of the Ministry of Religion, Jambi Province. This research uses qualitative research methods. Data collection techniques through interviews, observation and documentation. Interviews were conducted with 7 informants, and carried out from January to February 2023. Based on the data obtained, analysis was then carried out and grouped the data based on the topic of discussion. The results of this research show that the management of Hajj ritual guidance is carried out by the Regional Office of the Ministry of Religion of Jambi Province in Improving the quality of Hajj pilgrims is through: First, classifying Hajj pilgrims such as origin, age, education and occupation. Second, the Regional Office of the Ministry of Religion of Jambi Province provides guidance for Hajj pilgrims through the Regency/City Ministry of Religion, at the sub-district level, the Office of Religious Affairs (KUA).